A multi-objective approach for developing national energy efficiency plans - Haydt, Gustavo (2014)
This is a PDF file of an unedited manuscript that has been accepted for publication in Energy Policy. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. The final version will be available at: https://doi.org/10.1016/j.enpol.2013.06.133